Social Movements and ICTs: Addressing Complexity and Contingency - Gill, Gerard Andrew (Curtin University, 2017)
It is hard to deny that how Information and Communication Technologies are used by social movements is an issue of great importance. However, it is equally difficult to ascribe meaning to such use - it remains a contested topic within academia and in popular media. In this thesis I develop, demonstrate, and test a unique approach to studying ICT use in social movements which is informed by complexity theory and phronetic social science.